Evaluating a specialist education programme for nurses and allied health professionals working in older people care: A qualitative analysis of motivations and impact. (February 2021) - Fitzpatrick, Joanne M.; Hayes, Nicky; Naughton, Corina; Ezhova, Ivanka
Abstract: Background: Developing clinical leaders is essential for high-quality, safe care for older people. Fundamental to achieving this is specialist continuing professional development for nurses and allied health professionals. Objectives: To investigate the motivations of nurses and allied health professionals to undertake a national specialist gerontological programme, the Older Persons Fellowship, and its impacts on their development and on older people care. Design: A qualitative descriptive design. Methods: Participants were nurses and allied health professionals undertaking a national specialist gerontological programme in England. A purposive sample of 63 participants was recruited. Twelve focus groups and four individual interviews were conducted between February 2015 and February 2019. Data were analysed using thematic analysis. Results: Three themes were identified: credible gerontological experts; challenging ageism and suboptimal services; and legitimising gerontological practice as a speciality. Conclusions: Understanding the motivations to undertake a specialist gerontological programme and the impacts on practitioners and older people care and services will help inform the continuing professional development agenda for nurses and allied health professionals working in this field of practice. Policy makers, commissioners, managers, and educators can use the findings to inform continuing professional development priorities and provision for the gerontological workforce. Highlights: Nurses and allied health professionals in older people services want to be specialist practitioners in the field. Specialist knowledge and skills development, leadership of service transformation and innovation; and gerontological career progression. Investment in the continued development of gerontological nurses and allied health professionals is a necessity not a nicety.